Impact of Temporal and Spatial Variation on Odonata Communities in Northeastern Transboundary Hill Streams of Bangladesh, Including Two Newly Recorded Odonata Species in The Country (Bioresearch Communications, 2026)
Globally, dragonflies and damselflies (Odonata), are playing a significant ecological role as bioindicators of wetland health and as natural controller of pest and disease-vector populations. In Bangladesh, research focus on Odonata is not sufficient specially in the transboundary areas. In the hill streams and associated aquatic ecosystems support a rich diversity of Odonata species; however, comprehensive information on their diversity, distribution, ecology, and conservation status remains limited.  A comprehensive scientific ecological study of Odonata was conducted in the transboundary forest of the northeastern region of Bangladesh from July 2023 to June 2024. The study documented a total of 67 Odonata species, comprising 44 species (68%) from the suborder Anisoptera and 23 species (32%) from Zygoptera. Within Anisoptera, the family Libellulidae was the most diverse, accounting for 35 species (53.84%), while Coenagrionidae was the dominant family among Zygoptera, represented by 12 species (18.46%). Of the two surveyed locations, Site B (Non-distrubed) exhibited the highest species richness (56 species, 83.58%) and abundance (n = 1276), along with the highest values for both the Shannon-Wiener diversity index (H = 3.20) and Simpson’s index (Ds = 0.935). Seasonal analysis showed maximum species richness (63 species) and individual abundance (n = 1008) during the rainy season, while the winter season exhibited the highest evenness (E = 0.608). Orthetrum pruinosum emerged as the most dominant species overall (n = 289), especially in Site B, whereas Rhyothemis variegata was most frequently observed at Site A (n = 179). An Analysis of Similarities (ANOSIM) revealed a statistically significant variation (R = 0.551, p < 0.0001) in community composition between the two sites. One-way ANOVA indicated significant seasonal variation in species richness (F = 6.358, df = 2, p = 0.0043) and showed significant differences in abundance (F = 30.198, df = 2, p < 0.0001) between winter and the other two seasons (rainy and summer). Importantly, two Odonata species, Phyllothemis eltoni and Elattoneura campioni, were newly recorded in Bangladesh, marking the first national records for both genera, Phyllothemis and Elattoneura. These findings highlight hill stream of northeastern Bangladesh as a key Indo-Burma Odonata biodiversity landscape, requiring focused research and awareness for Odonata conservation.Bioresearch Commu. 12(2): 2162-2173, 2026 (January)